2017
DOI: 10.1055/s-0043-109098
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profile and Antiproliferative Effects in HaCaT Cells of a Salix reticulata Extract

Abstract: Phenolic constituents of (Salicaceae) and antiproliferative activity of an extract and individual compounds were investigated in immortalized human non-tumorigenic keratinocytes (HaCaT). A MeOH extract from aerial parts afforded several flavonoids, including luteolin and apigenin glycosides (- and ) and catechin (), two procyanidin fractions, and the phenolic glucosides picein (), triandrin (), and salicortin (). In an adenosine triphosphate assay, the MeOH extract reduced cell viability by approximately 60 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Peak 4 at 15.8 min corresponded to the known compound triandrin, in which m / z 357.1187 arises from its formate adduct and 311.1133 from its molecular ion [15]. Triandrin ( 4 ) has been recently found in the leaves and twigs of S. reticulata [16], but is better known in S. triandra [6,7], a parent of NWC1283. Compound 5 eluted at 16.3 min and showed m / z 371.1347 [M − H + HCOOH] − .…”
Section: Resultsmentioning
confidence: 99%
“…Peak 4 at 15.8 min corresponded to the known compound triandrin, in which m / z 357.1187 arises from its formate adduct and 311.1133 from its molecular ion [15]. Triandrin ( 4 ) has been recently found in the leaves and twigs of S. reticulata [16], but is better known in S. triandra [6,7], a parent of NWC1283. Compound 5 eluted at 16.3 min and showed m / z 371.1347 [M − H + HCOOH] − .…”
Section: Resultsmentioning
confidence: 99%
“…Using n-butanol as a solvent resulted in the separation of picein with 93.6% purity [ 93 ]. Another study performed on immortalized human non-tumorigenic keratinocytes (HaCaT) also showed that the other compounds of Salix reticulata significantly inhibited cell proliferation, whereas such an effect was not observed for picein [ 94 ]. They also used the MeOH extract from aerial parts and showed that MeOH extract with a concentration of 100 µg/ml reduced cell viability by about 60%, but the separation of the flavonoids and compounds failed to show any effect on cell proliferation for picein [ 94 ].…”
Section: Antioxidative and Neuroprotective Properties Of Piceinmentioning
confidence: 99%
“…Another study performed on immortalized human non-tumorigenic keratinocytes (HaCaT) also showed that the other compounds of Salix reticulata significantly inhibited cell proliferation, whereas such an effect was not observed for picein [ 94 ]. They also used the MeOH extract from aerial parts and showed that MeOH extract with a concentration of 100 µg/ml reduced cell viability by about 60%, but the separation of the flavonoids and compounds failed to show any effect on cell proliferation for picein [ 94 ]. Other compounds of Salix pseudo-lasiogyne twigs not including picein were also identified to have inhibitory effects against lipopolysaccharide-induced NO production in vitro (on microglial cells) and also significant antioxidative effects on lutathione reductase and superoxide dismutase production in vivo (on scopolamine-induced mice) [ 95 ].…”
Section: Antioxidative and Neuroprotective Properties Of Piceinmentioning
confidence: 99%
“…The protocol was similar to that described previously with some modifications [11,13,27]. The inserts for cell culture were positioned in 12-well plates.…”
Section: Wound-scratch Assay (Cell Migration Assay)mentioning
confidence: 99%